Assembléias de copépodes (CRUSTACEA: COPEPODA) na costa semiárida do Brasil: um enfoque sob duas redes de malha distintas - Santos, Nivia Maria Oliveira (2016)
Quantitative assessment of planktonic organisms is a key issue in determining food web structure and material cycling in pelagic ecosystems, however the problem of the choice of sampler for quantitative plankton collection is not an easy one. Selection of a net with appropriate mesh size is necessary for reliable estimation of zooplankton abundance and biomass. The aim of this study was to investigate copepods sampled with 120 and 300 μ m simple net with a focus on selectivity of sampling method. Samples were taken on the inner continental shelf, at 18 stations parallel to the shore. All sampling procedures were made in July and October 2010, in continental shelf of Ceará, Piauí and Maranhão States (Semiarid Brazilian Coast). The results from analysis showed the occurrence of 34 taxa. The average abundance of copepods sampled with 120 μ m net was 54.71±150.38 ind.m-3 and with 300 μ m net was 9.67±41.21 ind.m-3 . Species richness, dominance and density are higher in 120 μm net. In 300 μ m net, the number of exclusive taxa was higher. Venn diagram shows that early stages of copepods were recorded by 62.5% of exclusive taxa in 120 μm net, while only 40% in 300 μ m net. Total copepods abundance sampled by 120 μm net was six times higher than the one sampled by 300 μm net. 120μm net was more efficient in the capture of small copepods and early developmental stages of copepods. Larger and adults copepods were sampled by 300 μ m net. The main taxa sampled in 120 µm net were Oithona spp., Euterpina acutifrons, Paracalanus aculeatus. These taxa also were sampled in 300 µm net, but their abundance was lower. To improving our understanding of copepod biology and ecology, it is recommended that at least two different net be used in order to sample copepods size ranges.